Pengaruh Good Corporate Governence dan Firm Size terhadap Pengungkapan Sustainability Report pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Oktapiani, Nabila; Simatupang, Frido Saritua (Universitas Batanghari, 2024)
Companies or profit entities have the main goal of maximizing profits, but now this goal has shifted from how companies only want to get profits to how companies manage their social and environmental impacts. In Indonesia itself, not many companies disclose their sustainability reports. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange for a 3-year period, namely 2020-2022. The sampling technique used was purposive sampling. The data analysis method used is multiple linear regression. Sustainability report disclosure in this study uses GRI Standards 2021. The independent board of commissioners and institutional ownership have no effect on the disclosure of the Sustainability report, then, the audit committee and firm size affect the disclosure of the Sustainability report. then simultaneously the independent board of commissioners, institutional ownership, audit committee, and Firm Size have a significant effect on the disclosure of the Sustainability report.